(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Introduction. The main problem in the research area is the fundamental need for fundamentalization, the continuity of education, the use of experience accumulated by the education system, and the maximum expansion and implementation in educational processes of information technology education and computer technology, both at the educational level and at the level of management of them. Purpose. Nowadays in conditions of development and functioning of the educational system, the necessity of qualitative improvement of informational and analytical support in the educational system institutions, including educational processes at all levels, is objectively overdue. The effectiveness of informational and analytical systems, in turn, objectively determines the level of awareness of specific subjects of management in educational institutions. Methods. The main directions in his work are the following ones: informational and analytical direction – provision in educational establishments of conditions for the introduction of pedagogical technologies, organization of teacher’s innovative activity, the conditions under which a deep analysis of their own activities becomes a conscious necessity; consulting and informational direction – studying documents on education, school development. Providing assistance to teachers in material planning, developing lessons, streamlining the learning process, modular training, drawing up technological maps with prediction of desired results, teaching a teacher to conduct diagnostics; diagnostic and analytical direction – monitoring is the basis of the foundation in the management of the educational process. Results. The article substantiates the concept of «informational and analytical competence of primary school teachers», defines its content and structure, principles and methods of management. Originality. Nowadays, a new system point of view is needed for the organization and management of educational and educational processes within the education system, which should consist of interconnected subsystems, which are united by the general purpose of functioning. Conclusion. The solution of this problem is focused on the use of information and analytical support systems that meet the modern requirements in the educational sphere.